A constructivist approach to teaching scientific content to university students - Ziani, Melouka; Aoumeur, Hayat (Technium Social Sciences Journal, 2022)
The constructivist approach to acquiring new knowledge has very much been appreciated by foreign language practitioners for optimal learning. The E-Model, developed by Atkins & Karplus (1962) as a research-based approach implies that the learners construct new knowledge on their own (Lynch, 2017). The present paper then suggests the implementation of the instructional E-Model in teaching scientific content to Master students through a Self-Directed Approach. The study is exploratory and experimental in its scope and aims at unleashing university students’ desire to construct new knowledge through a reflective model composed of a set of stages: engagement, exploration, explanation, elaboration, and evaluation. Participant observation was used as a tool to obtain qualitative data. The findings demonstrated that the E-Model was effective as a constructivist teaching approach for a great majority of the students, and this was reflected through their skills in presenting and manipulating new information. In addition to their cognitive development, the students’ self-confidence and self-esteem were very much enhanced.